20 years after the embodied mind-why is cognitivism alive and kicking? - Müller, Vincent C. (Re-Conceptualizing Mental "Illness": The View from Enactivist Philosophy and Cognitive Science - AISB Convention 2013, 2013)
I want to suggest that the major influence of classical arguments for embodiment like "The Embodied Mind" by Varela, Thomson & Rosch (1991) has been a changing of positions rather than a refutation: Cognitivism has found ways to retreat and regroup at positions that have better fortification, especially when it concerns theses about artificial intelligence or artificial cognitive systems. For example: a) Agent-based cognitivism' that understands humans as taking in representations of the world, doing rule-based processing and then acting on them (sense-plan-act) is often limited to conscious decision processes; and b) Purely syntactic cognition is compatible with embodiment, or supplemented by embodiment (e.g. for 'grounding'). While the empirical thesis of embodied cognition ('embodied cognitive science') is true and the practical engineering thesis ('morphological computation', 'cheap design') is often true, the conceptual thesis ('embodiment is necessary for cognition') is likely false - syntax is often enough for cognition, unless grounding is really necessary. I conclude that it has become more sensible to integrate embodiment with traditional approaches rather than "fight for embodiment" or "against cognitivism".
CRIS-Team Scopus Importer:2022-06-20

AI AS IA: The use and abuse of artificial intelligence (AI) for human enhancement through intellectual augmentation (IA) - Erler, Alexandre; Müller, Vincent C. (The Routledge Handbook of the Ethics of Human Enhancement, 2023)
This paper offers an overview of the technological possibilities and ethics of using AI to achieve human enhancement and more broadly what we call intellectual augmentation (IA). After explaining the central notions of human enhancement, IA, and AI, we discuss the main and most recent technologies for IA, with or without brain-computer interfaces. Given this picture, this paper discusses potential ethical problems, namely inadequate performance, safety, coercion and manipulation, privacy, cognitive liberty, authenticity, and fairness, in more detail. This paper concludes that while there are very significant technical hurdles to real human enhancement through AI, and significant ethical problems, there are also significant benefits that may realistically be achieved in ways that are consonant with a rights-based ethics as well. This paper also highlights the specific concerns that apply particularly to applications of AI for “sheer” IA (more realistic in the near term) and to enhancement applications, respectively.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Engineering & Technology; Health and Social Care; Humanities; Medicine; Dentistry; Nursing & Allied Health; Politics & International Relations; Social Sciences; Sports and Leisure

Autonomous Cognitive Systems in Real-World Environments: Less Control, More Flexibility and Better Interaction - Müller, Vincent C. (Cognitive Computation, 2012)
In October 2011, the "2nd European Network for Cognitive Systems, Robotics and Interaction", EUCogII, held its meeting in Groningen on "Autonomous activity in real-world environments", organized by Tjeerd Andringa and myself. This is a brief personal report on why we thought autonomy in real-world environments is central for cognitive systems research and what I think I learned about it. The theses that crystallized are that (a) autonomy is a relative property and a matter of degree, (b) increasing autonomy of an artificial system from its makers and users is a necessary feature of increasingly intelligent systems that can deal with the real world and (c) more such autonomy means less control but at the same time improved interaction with the system. © 2012 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-06-20
Keywords: Autonomy; Cognitive system; Flexibility; HCI; Human-computer interaction

Autonomous killer robots are probably good news - Müller, Vincent C. (Taylor and Francis, 2016)
The European Parliament has called for a moratorium or ban of lethal autonomous weapon systems (LAWS). Robotics in warfare will be a major change, comparable to the introduction of planes or perhaps even nuclear weapons. One of the questions is whether the use of robotics, especially highly autonomous robotics, constitutes just one major step in the arms race or a step that introduces qualitatively new ethical concerns. This chapter provides a general recommendation on the issue of whether killer robots should be banned. Killer robots are attractive to the military and to political funding for a number of reasons: they reduce the risk to one’s own soldiers, reducing the human and political costs of war. Killer robots, like any weapon in war, must comply with the regulations of International Humanitarian Law in the Geneva Convention.
CRIS-Team Scopus Importer:2022-06-20

Autonomous killer robots are probably good news - Simpson, Thomas W.; Müller, Vincent C. (Frontiers in Artificial Intelligence and Applications, 2014)
Will future lethal autonomous weapon systems (LAWS) or 'killer robots', be a threat to humanity? In this policy paper, we argue that they do not take responsibility away from humans; in fact they increase the ability to hold humans accountable for war crimes. Also, using LAWS in war, as compared to a war without them, would probably make wars a bit less bad through an overall reduction of human suffering, especially in civilians. Finally, the availability of LAWS would probably not increase the probability of war or other lethal conflict-especially as compared to extant remote-controlled weapons. The European Parliament and a UN special rapporteur have called for a moratorium or ban of LAWS, supported by the vast majority of writers and campaigners on the issue. The 'Contracting Parties to the Geneva Convention at the United Nations' are presently discussing such a ban. However, the main arguments in favour of a ban are unsound. We are afraid of killer robots, but we should not be: They are probably good news.
CRIS-Team Scopus Importer:2022-06-20
Keywords: just war requirements; killer robots; LAWS; policy recommendations on autonomous wapons; responsibility; utility considerations

Basic Issues in AI Policy - Müller, Vincent C. (Interactive Robotics: Legal, Ethical, Social and Economic Aspects, 2022)
This short paper summarises some of the basic points of AI ethics and policy as they present themselves now. We explain the notion of AI, the main ethical issues in AI and the main policy aims and means.
CRIS-Team Scopus Importer:2022-06-20

Deep opacity undermines data protection and explainable artificial intelligence - Müller, Vincent C. (AISB Convention 2021: Communication and Conversations, 2021)
It is known that big data analytics and AI pose another threat to privacy, and it is known that there is some kind of ‘black box problem’ in AI. I propose that (1) the ‘black box’ becomes the ‘black box problem’ in a context of justification for judgments and actions, crucially in the context of privacy. (2) This will suggest distinguishing two kinds of classic opacity and introducing a third: The subjects may not know what the system does (‘shallow opacity’), the analysts may not know what the system does (‘standard black box opacity’), or even the analysts cannot possibly know what the system might do (‘deep opacity’). (3) If the agents, data subjects as well as analytics experts, operate under opacity, then they cannot provide some of the justifications for judgments that are necessary to protect privacy – e.g. they cannot give “informed consent” or assert “anonymity”. It follows from (2) and (3) that agents in big data analytics and AI, often cannot make the judgments needed to protect privacy. So big data analytics makes the privacy problems worse, and the remedies less effective. Closing, I provide a brief outlook on technical ways to handle this situation.
CRIS-Team Scopus Importer:2022-06-20
Keywords: Big data analytics; Black box problem; Deep opacity; Explainable AI; Justification; Opacity; Privacy

Editorial: Risks of artificial intelligence - Muller, Vincent C. (CRC Press, 2016)
CRIS-Team Scopus Importer:2023-03-08

Ethics of artificial intelligence - Müller, Vincent C. (Taylor and Francis Inc., 2021)
CRIS-Team Scopus Importer:2022-06-20

Existential risk from AI and orthogonality: Can we have it both ways? - Muller, Vincent C.; Cannon, Michael (Ratio, 2022)
The standard argument to the conclusion that artificial intelligence (AI) constitutes an existential risk for the human species uses two premises: (1) AI may reach superintelligent levels, at which point we humans lose control (the ‘singularity claim’); (2) Any level of intelligence can go along with any goal (the ‘orthogonality thesis’). We find that the singularity claim requires a notion of ‘general intelligence’, while the orthogonality thesis requires a notion of ‘instrumental intelligence’. If this interpretation is correct, they cannot be joined as premises and the argument for the existential risk of AI turns out invalid. If the interpretation is incorrect and both premises use the same notion of intelligence, then at least one of the premises is false and the orthogonality thesis remains itself orthogonal to the argument to existential risk from AI. In either case, the standard argument for existential risk from AI is not sound.—Having said that, there remains a risk of instrumental AI to cause very significant damage if designed or used badly, though this is not due to superintelligence or a singularity.
CRIS-Team Scopus Importer:2022-06-20
Keywords: existential risk; general intelligence; instrumental intelligence; orthogonality; singularity; superintelligence

Foreword from the workshop chairs - Müller, Vincent C.; Ayesh, Aladdin; Bishop, Mark; Barnden, John; Plebe, Alessio; Perconti, Pietro; Arrabales, Raul; Chella, Antonio; Trautteur, Giuseppe; Rzepka, Rafal (AISB/IACAP World Congress 2012: Revisiting Turing and His Test: Comprehensiveness, Qualia, and the Real World, Part of Alan Turing Year 2012, 2012)
CRIS-Team Scopus Importer:2022-06-20

From embodied and extended mind to no mind - Müller, Vincent C. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2012)
The paper will discuss the extended mind thesis with a view to the notions of "agent" and of "mind", while helping to clarify the relation between "embodiment" and the "extended mind". I will suggest that the extended mind thesis constitutes a reductio ad absurdum of the notion of 'mind'; the consequence of the extended mind debate should be to drop the notion of the mind altogether - rather than entering the discussion how extended it is. © 2012 Springer-Verlag.
CRIS-Team Scopus Importer:2022-06-20

Future Progress in Artificial Intelligence: A Survey of Expert Opinion - Bostrom, Nick; Müller, Vincent C. (Springer Science and Business Media B.V., 2016)
There is, in some quarters, concern about high–level machine intelligence and superintelligent AI coming up in a few decades, bringing with it significant risks for humanity. In other quarters, these issues are ignored or considered science fiction. We wanted to clarify what the distribution of opinions actually is, what probability the best experts currently assign to high–level machine intelligence coming up within a particular time–frame, which risks they see with that development, and how fast they see these developing. We thus designed a brief questionnaire and distributed it to four groups of experts in 2012/2013. The median estimate of respondents was for a one in two chance that high-level machine intelligence will be developed around 2040–2050, rising to a nine in ten chance by 2075. Experts expect that systems will move on to superintelligence in less than 30 years thereafter. They estimate the chance is about one in three that this development turns out to be ‘bad’ or ‘extremely bad’ for humanity.
CRIS-Team Scopus Importer:2022-06-20
Keywords: AI; Artificial intelligence; Expert opinion; Future of AI; Humanity; Intelligence explosion; Machine intelligence; Opinion poll; Progress; Singularity; Superintelligence

Interaction and resistance: The recognition of intentions in new human-computer interaction - Müller, Vincent C. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2011)
Just as AI has moved away from classical AI, human-computer interaction (HCI) must move away from what I call 'good old fashioned HCI' to 'new HCI' - it must become a part of cognitive systems research where HCI is one case of the interaction of intelligent agents (we now know that interaction is essential for intelligent agents anyway). For such interaction, we cannot just 'analyze the data', but we must assume intentions in the other, and I suggest these are largely recognized through resistance to carrying out one's own intentions. This does not require fully cognitive agents but can start at a very basic level. New HCI integrates into cognitive systems research and designs intentional systems that provide resistance to the human agent. © 2011 Springer.
CRIS-Team Scopus Importer:2022-06-20
Keywords: AI; cognitive systems; Human-computer interaction; intelligence; interaction; resistance; systems design

Introduction: Philosophy and theory of artificial intelligence - Müller, Vincent C. (Minds and Machines, 2012)
CRIS-Team Scopus Importer:2022-06-20

Is it time for robot rights? Moral status in artificial entities - Muller, Vincent C. (Ethics and Information Technology, 2021)
Some authors have recently suggested that it is time to consider rights for robots. These suggestions are based on the claim that the question of robot rights should not depend on a standard set of conditions for ‘moral status’; but instead, the question is to be framed in a new way, by rejecting the is/ought distinction, making a relational turn, or assuming a methodological behaviourism. We try to clarify these suggestions and to show their highly problematic consequences. While we find the suggestions ultimately unmotivated, the discussion shows that our epistemic condition with respect to the moral status of others does raise problems, and that the human tendency to empathise with things that do not have moral status should be taken seriously—we suggest that it produces a “derived moral status”. Finally, it turns out that there is typically no individual in real AI that could even be said to be the bearer of moral status. Overall, there is no reason to think that robot rights are an issue now.
CRIS-Team Scopus Importer:2022-06-20
Keywords: AI; AMA; Artificial intelligence; Artificial moral agent; Ethical behaviourism; Ethics; Moral agent; Moral consideration; Moral patient; Moral status; Orchestration; Person; Relational turn; Rights; Robot

Just War and Robots' Killings - Simpson, Thomas W.; Müller, Vincent C. (Philosophical Quarterly, 2016)
May lethal autonomous weapons systems-'killer robots'-be used in war? The majority of writers argue against their use, and those who have argued in favour have done so on a consequentialist basis. We defend the moral permissibility of killer robots, but on the basis of the non-Aggregative structure of right assumed by Just War theory. This is necessary because the most important argument against killer robots, the responsibility trilemma proposed by Rob Sparrow, makes the same assumptions. We show that the crucial moral question is not one of responsibility. Rather, it is whether the technology can satisfy the requirements of fairness in the redistribution of risk. Not only is this possible in principle, but some killer robots will actually satisfy these requirements. An implication of our argument is that there is a public responsibility to regulate killer robots' design and manufacture.
CRIS-Team Scopus Importer:2022-06-20
Keywords: killer robots; lethal automated weapons systems; responsibility trilemma; risk imposition; tolerance level.

Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics): Preface - Esposito, Anna; Esposito, Antonietta M.; Vinciarelli, Alessandro; Hoffmann, Rüdiger; Müller, Vincent C. (Cognitive Behavioural Systems - COST 2102 International Training School, Revised Selected Papers, 2012)
CRIS-Team Scopus Importer:2022-06-20

Legal vs. ethical obligations–a comment on the EPSRC’s principles for robotics - Müller, Vincent C. (Connection Science, 2017)
While the 2010 EPSRC principles for robotics state a set of five rules of what “should” be done, I argue they should differentiate between legal obligations and ethical demands. Only if we make this difference can we state clearly what the legal obligations already are, and what additional ethical demands we want to make. I provide suggestions how to revise the rules in this light and how to make them more structured.
CRIS-Team Scopus Importer:2022-06-20
Keywords: killer robots; legal obligation; principles of robotics; Robot ethics; robot law

Measuring Progress in Robotics: Benchmarking and the ‘Measure-Target Confusion’ - Müller, Vincent C. (Metrics of Sensory Motor Coordination and Integration in Robots and Animals, 2020)
While it is often said that in order to qualify as a true science robotics should aspire to reproducible and measurable results that allow benchmarking, I argue that a focus on benchmarking will be a hindrance for progress. Several academic disciplines that have been led into pursuing only reproducible and measurable ‘scientific’ results—robotics should be careful not to fall into that trap. Results that can be benchmarked must be specific and context-dependent, but robotics targets whole complex systems independently of a specific context—so working towards progress on the technical measure risks missing that target. It would constitute aiming for the measure rather than the target: what I call ‘measure-target confusion’. The role of benchmarking in robotics shows that the more general problem to measure progress towards more intelligent machines will not be solved by technical benchmarks; we need a balanced approach with technical benchmarks, real-life testing and qualitative judgment.
CRIS-Team Scopus Importer:2022-06-20

New Developments in the Philosophy of AI - Müller, Vincent C. (Springer Science and Business Media B.V., 2016)
The philosophy of AI has seen some changes, in particular: (1) AI moves away from cognitive science, and (2) the long term risks of AI now appear to be a worthy concern. In this context, the classical central concerns – such as the relation of cognition and computation, embodiment, intelligence & rationality, and information – will regain urgency.
CRIS-Team Scopus Importer:2022-06-20
Keywords: AI risk; Cognitive science; Computation; Embodiment; Philosophy of AI; Philosophy of artificial intelligence; Rationality; Superintelligence

Pancomputationalism: Theory or metaphor? - Müller, Vincent C. (Taylor and Francis, 2015)
CRIS-Team Scopus Importer:2022-06-20

Risks of artificial intelligence - Muller, Vincent C. (CRC Press, 2016)
If the intelligence of artificial systems were to surpass that of humans, humanity would face significant risks. The time has come to consider these issues, and this consideration must include progress in artificial intelligence (AI) as much as insights from AI theory.
CRIS-Team Scopus Importer:2023-03-08

Risks of general artificial intelligence - Müller, Vincent C. (Journal of Experimental and Theoretical Artificial Intelligence, 2014)
The papers in this special volume of the Journal of Experimental and Theoretical Artificial Intelligence are the outcome of a conference on the 'Impacts and Risks of Artificial General Intelligence' (AGI-Impacts) that took place at the University of Oxford, on 10 and 11 December 2012. Schneier presented the theory from his new book Liars and Outliers: Enabling the Trust that Society Needs to Thrive that security needs to mature to a wider discipline, which crucially relies on establishing and maintaining trust, a trust that is undermined by many, including state agents. The paper by Omohundro introduces the problem of risk and the author presses his point that even an innocuous artificial agent, like one programmed to win chess games, can very easily turn into a serious threat for humans. B. Goertzel explains how his 'Goal-Oriented Learning Meta-Architecture' may be capable of preserving its initial caring goals while learning and improving its general intelligence.
CRIS-Team Scopus Importer:2022-06-20

Simple or complex bodies? Trade-offs in exploiting body morphology for control - Hoffmann, Matej; Müller, Vincent C. (Representation and Reality in Humans, Other Living Organisms and Intelligent Machines, 2017)
Engineers fine-tune the design of robot bodies for control purposes; however, a methodology or set of tools is largely absent, and optimization of morphology (shape, material properties of robot bodies, etc.) is lagging behind the development of controllers. This has become even more prominent with the advent of compliant, deformable or ‘soft’ bodies. These carry substantial potential regarding their exploitation for control—sometimes referred to as ‘morphological computation’. In this article, we briefly review different notions of computation by physical systems and propose the dynamical systems framework as the most useful in the context of describing and eventually designing the interactions of controllers and bodies. Then, we look at the pros and cons of simple versus complex bodies, critically reviewing the attractive notion of ‘soft’ bodies automatically taking over control tasks. We address another key dimension of the design space—whether model-based control should be used and to what extent it is feasible to develop faithful models for different morphologies.
CRIS-Team Scopus Importer:2022-06-20

The ethical imperatives of the COVID-19 pandemic: A review from data ethics Los imperativos éticos de la pandemia de COVID-19: Un análisis desde la ética de los datos - Bruneau, Gabriela Arriagada; Gilthorpe, Mark; Müller, Vincent C. (Veritas : Revista de Filosofía y Teología, 2020)
In this review, we present some ethical imperatives observed in this pandemic from a data ethics perspective. Our exposition connects recurrent ethical problems in the discipline, such as, privacy, surveillance, transparency, accountability, and trust, to broader societal concerns about equality, discrimination, and justice. We acknowledge data ethic’s role as significant to develop technological, inclusive, and pluralist societies.
CRIS-Team Scopus Importer:2022-06-20
Keywords: Accountability; COVID-19; Data ethics; Data governance; Digital divide; Digital epidemiology; Equality; Fairness; Privacy; Transparency; Vulnerability

The History of Digital Ethics - Müller, Vincent C. (Oxford Handbook of Digital Ethics, 2023)
Digital ethics, also known as computer ethics or information ethics, is now a lively field that draws a lot of attention. But what were the developments that led to its existence and present state? What are the traditions, concerns, and technological and social developments that guided digital ethics? How did ethical issues change with the digitalization of human life? How did the traditional discipline of philosophy respond and how was ‘applied ethics’ influenced by these developments? This chapter proposes to view the history of digital ethics in three phases: pre-digital modernity (before the invention of digital technology), digital modernity (with digital technology but analogue lives), and digital post-modernity (with digital technology and digital lives). For each phase, the developments in digital ethics are explained with the background of the technological and social conditions. Finally, a brief outlook is provided.<br
CRIS-Team Scopus Importer:2024-12-16
Keywords: digitalization; applied ethics; pre-digital modernity; digital modernity; digital post-modernity; digital ethics; computer ethics; information ethics

What is a digital state? - Müller, Vincent C. (6th AISB Symposium on Computing and Philosophy: The Scandal of Computation - What is Computation? - AISB Convention 2013, 2013)
There is much discussion about whether the human mind is a computer, whether the human brain could be emulated on a computer, and whether at all physical entities are computers (pancomputationalism). These discussions, and others, require criteria for what is digital. 1 I propose that a state is digital if and only if it is a token of a type that serves a particular function - typically a representational function for the system. This proposal is made on a syntactic level, assuming three levels of description (physical, syntactic, semantic). It suggests that being digital is a matter of discovery or rather a matter of how we wish to describe the world, if a functional description can be assumed. Given the criterion provided and the necessary empirical research, we should be in a position to decide on a given system (e.g. the human brain) whether it is a digital system and can thus be reproduced in a different digital system (since digital systems allow multiple realization).
CRIS-Team Scopus Importer:2022-06-20

What Is Morphological Computation? On How the Body Contributes to Cognition and Control - Müller, Vincent C.; Hoffmann, Matej (Artificial Life, 2017)
The contribution of the body to cognition and control in natural and artificial agents is increasingly described as "offloading computation from the brain to the body," where the body is said to perform "morphological computation." Our investigation of four characteristic cases of morphological computation in animals and robots shows that the "offloading" perspective is misleading. Actually, the contribution of body morphology to cognition and control is rarely computational, in any useful sense of the word. We thus distinguish (1) morphology that facilitates control, (2) morphology that facilitates perception, and the rare cases of (3) morphological computation proper, such as reservoir computing, where the body is actually used for computation. This result contributes to the understanding of the relation between embodiment and computation: The question for robot design and cognitive science is not whether computation is offloaded to the body, but to what extent the body facilitates cognition and control - how it contributes to the overall orchestration of intelligent behavior.
CRIS-Team Scopus Importer:2022-06-20
Keywords: Body; Cognition; Computation; Control; Embodiment; Soft robotics

Which symbol grounding problem should we try to solve? - Müller, Vincent C. (Journal of Experimental and Theoretical Artificial Intelligence, 2015)
Floridi and Taddeo propose a condition of 'zero semantic commitment' for solutions to the grounding problem, and a solution to it. I argue briefly that their condition cannot be fulfilled, not even by their own solution. After a look at Luc Steel's very different competing suggestion, I suggest that we need to re-think what the problem is and what role the goals in a system play in formulating the problem. On the basis of a proper (syntactic) understanding of computing, I come to the conclusion that the only sensible grounding problem is how we can explain and re-produce the behavioural ability and function of meaning in artificial computational agents.
CRIS-Team Scopus Importer:2022-06-20
Keywords: Chinese room; grounding; semantic commitment; symbol grounding

Would you mind being watched by machines? Privacy concerns in data mining - Müller, Vincent C. (AI and Society, 2009)
Data mining is not an invasion of privacy because access to data is only by machines, not by people: this is the argument that is investigated here. The current importance of this problem is developed in a case study of data mining in the USA for counterterrorism and other surveillance purposes. After a clarification of the relevant nature of privacy, it is argued that access by machines cannot warrant the access to further information, since the analysis will have to be made either by humans or by machines that understand. It concludes that the current data mining violates the right to privacy and should be subject to the standard legal constraints for access to private information by people. © Springer-Verlag London Limited 2007.
CRIS-Team Scopus Importer:2022-06-20